2015
DOI: 10.1002/pmic.201500120
|View full text |Cite
|
Sign up to set email alerts
|

Skin mucus proteome map of European sea bass (Dicentrarchus labrax)

Abstract: Abbreviations: AFP, antifreeze proteins; APOA1, Apolipoprotein A1; ASC, apoptosisassociated speck-like protein containing a caspase recruitment domain; C3, complement component 3; CALM, calmodulin; CALR, calreticulin; CASP, caspase; cDNA, complementary DNA; ERp57,endoplasmic reticulum protein 57; FBL, fucose-binding lectin; H1/4, histone H1/H4; IL1B, interleukin 1-beta; LEI, leukocyte elastase inhibitor; LYZ, lysozyme; qPCR, real-time PCR; PRDX, peroxiredoxin; SOD superoxide dismutase; TF, transferrin; WAP65, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 82 publications
4
97
0
Order By: Relevance
“…Although no differences in this respect were observed between ventral and dorsal skin in the present study, knowledge of constitutive transcript levels in both regions may be useful for saying the susceptibility of specific regions to stressors, as we showed for ventral skin in a previous study regarding the cytokine expression profile [19]. In addition, a previous study in European sea bass identified lyz , casp1 , lei , hsp70 , nkef1 , nkef2 and gst in skin mucus and evaluated their expression in the skin [10], so these molecules seem to be conserved across species.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Although no differences in this respect were observed between ventral and dorsal skin in the present study, knowledge of constitutive transcript levels in both regions may be useful for saying the susceptibility of specific regions to stressors, as we showed for ventral skin in a previous study regarding the cytokine expression profile [19]. In addition, a previous study in European sea bass identified lyz , casp1 , lei , hsp70 , nkef1 , nkef2 and gst in skin mucus and evaluated their expression in the skin [10], so these molecules seem to be conserved across species.…”
Section: Resultssupporting
confidence: 68%
“…For this reason, we chose molecules previously reported in skin mucus of teleost, such as the immunoglobulins, ighm and ight [31], which are the major components of the adaptive immune system; as well as other important immune-related markers such as lyz , casp1 , lei , hsp70 , nkef1 , nkef2 and gst , which were found at proteomic level in our previous skin mucus studies [10,14]. The greatest differences between dorsal and ventral regions at transcript level were observed in the immunoglobulin specialized in mucosal immunology [32], ight , with lower levels in the ventral skin than in the dorsal region (Fig 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that this protein was previously identified in skin mucus of gilthead seabream [19], to our knowledge this is the first time that over-expression has been found after any probiotic diet, Pdp11 in this study. In addition, this protein has also reported in skin mucus of teleosts such as European sea bass [18] or Atlantic cod [34] but further studies are needed to clarify its implication in skin mucus.…”
mentioning
confidence: 99%